One reaction-two types of polymerization mechanisms for N-vinyl carbazole using a single donor–acceptor initiating system. (May 2015) - Rusen, Edina; Mocanu, Alexandra; Diacon, Aurel
Graphical abstract: Highlights: A CTC, able to participate in a polymerization reaction by two types of mechanism, is formed. The radical as well as cationic polymerization mechanisms have been highlighted. The proposed kinetic model has been validated by the experimental data. The donor:acceptor ratio influences the percentage of the two types of polymerization mechanism. The CTC has been investigated by UV–VIS. Abstract: Based on the electron-donating properties of N-vinyl carbazole and electron-accepting capacity of dichlorobenzene, the first step of the study consisted in the mixing of the two components. As a result, it is formed a charge transfer complex (CTC) able to participate in a polymerization reaction by two types of mechanism. Radical as well as cationic polymerization mechanisms have been highlighted. The proposed kinetic model has been validated by the experimental data. The donor:acceptor ratio and the reaction medium influence the proportion of the two types of polymerization mechanism, as confirmed by the GPC analysis. The CTC has been investigated by UV–VIS.